The value of De Ritis ratio in patients undergoing percutaneous coronary intervention for prediction of contrast-associated acute kidney injury - Noher M. Abass*; Mohamed H. El-Rashidy (SVU - International Journal of Medical Sciences, 2023)
Background: The most serious side effect of percutaneous coronary intervention (PCI) is contrast-associated acute kidney damage (CA-AKI), an injury to the kidneys caused by the body's reaction to the contrast chemicals that were injected into the bloodstream. Objectives: The purpose of this trial was to assess the correlation among the De-Ritis ratio & CA-AKI in PCI. Patients and methods: Five hundred people with ischemic heart disease (IHD) who had PCI were included in this study. Complete medical histories and physical examinations were performed on all individuals. Upon admittance, or the following morning, blood routine testing, aspartate aminotransferase, fasting lipid profile, samples from blood were taken for alanine aminotransferase, international normalized ratio, bilirubin, fasting blood glucose, evaluation of Uric Acid in the Blood. The aspartate aminotransferase-to-alanine aminotransferase ratio was determined by aspartate aminotransferase (AST) activity (U/L)/ALT alanine aminotransferase (U/L). Results: A total number of 500 cases undergoing elective PCI was enrolled. Mean of Model for End Stage Lived Disease (MELD) score was 7.25 & ranged from 7 to 9 and Mean of Model for End Stage Lived Disease excluding INR (MELD-XI) score was 9.97 and ranged from 9 to 11. A total of 35 (7%) patients developed AKI. AST/ALT ratio can detect AKI at cutoff 1.1 with sensitivity, specificity was 100%, and 58.1% respectively (p< 0.001) and AUC was 0.761 as illustrated in table (3) and figure (1). ALT can detect AKI at cutoff 19 with sensitivity, specificity was 100%, and 81.7% respectively (p< 0.001) and AUC was 0.896. Model for End-Stage Liver Disease score can detect AKI at cutoff 7 with sensitivity, specificity was 42.9%, and 77.4% respectively (p< 0.001) and AUC was 0.608. MELD excluding international normalized ratio score can detect AKI at cutoff 9 with sensitivity, specificity was 42.9%, and 82.8% respectively (p< 0.001) and AUC (Area under the curve) was 0.677. ALT had the best AUC followed by aspartate aminotransferase to alanine aminotransferase ratio then Model for End-Stage Liver Disease -XI scores and MELD score. Conclusion: Long-term unfavorable clinical results are related with a high De Ritis ratio among individuals receiving elective PCI, as well a cut off value of over 1.1 makes the De Ritis ratio a good predictor for CA-AKI.